2000
DOI: 10.1093/emboj/19.20.5440
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Type Ialpha PIPkinase with phospholipase D: a role for the local generation of phosphatidylinositol 4,5-bisphosphate in the regulation of PLD2 activity

Abstract: Phosphoinositides are localized in various intracellular compartments and can regulate a number of intracellular functions, such as cytoskeletal dynamics and membrane traf®cking. Phospholipase Ds (PLDs) are regulated enzymes that hydrolyse phosphatidylcholine (PtdCho) to generate the putative second messenger phosphatidic acid (PtdOH). In vitro, PLDs have an absolute requirement for higher phosphorylated inositides, such as phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ]. Whether this lipid is able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 74 publications
3
72
1
Order By: Relevance
“…This conclusion is supported by evidence of an interdependent relationship between PA production by phospholipase D isoforms and PI(4,5)P2 production by the type I PIP5Ks in the regulation of endocytosis and in response to the small G-protein ARF6 [Arneson et al, 1999;Divecha et al, 2000]. Since, type I PIP5K activity is stimulated by PA and PI(4,5)P2 activates phospholipase D, a positive feedback loop is potentially formed between these enzyme families.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This conclusion is supported by evidence of an interdependent relationship between PA production by phospholipase D isoforms and PI(4,5)P2 production by the type I PIP5Ks in the regulation of endocytosis and in response to the small G-protein ARF6 [Arneson et al, 1999;Divecha et al, 2000]. Since, type I PIP5K activity is stimulated by PA and PI(4,5)P2 activates phospholipase D, a positive feedback loop is potentially formed between these enzyme families.…”
Section: Discussionmentioning
confidence: 76%
“…The observation that ARF GTPases regulate both phospholipase D enzymes and PIP5Ks together with evidence that PA and PI(4,5)P2 regulate overlapping cellular functions suggests that an intimate connection exists between these enzyme families [Honda et al, 1999;Brown et al, 2001;Skippen et al, 2002]. Consistent with this notion, PIP5K-Ia directly associates with both phospholipase D1 and phospholipase D2 and recruits phospholipase D2 to intracellular vesicles [Divecha et al, 2000]. Additionally, ARF1 mutants that fail to bind phospholipase D do not enhance PI(4,5)P2 production in vivo as effectively as wildtype ARF1 [Skippen et al, 2002].…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…For example, PA can reportedly promote the membrane association and activation of Raf-1, member of the Erk mitogen-activated protein kinase cascade (Ghosh et al, 1996). Other reported protein targets of PA are phosphatidylinositol 5-kinase (Divecha et al, 2000), NADPH oxidase (Palicz et al, 2001), mTOR (Fang et al, 2001), Pak1 (Symons, 2000), and sphingosine kinase 1 (Delon et al, 2004). In addition, PA is rapidly metabolized to other lipids with biological activity.…”
mentioning
confidence: 99%
“…Most studies have found PLD2 is mainly localized in the plasma membrane (Du et al, 2004) and that PLD1 is primarily localized in specialized vesicles, such as, endoplasmic reticulum (ER), Golgi apparatus, secretory vesicles, endosomes, and lysosomes (Brown et al, 1998;Freyberg et al, 2001), and several reports indicate that PLD2 is also localized in cytoplasmic vesicles (Divecha et al, 2000). In addition, PLD2 can be translocated into the submembranous vesicles by serum and ruffling membranes by epidermal growth factor (EGF) (Colley et al, 1997;Honda et al, 1999).…”
Section: Localisationmentioning
confidence: 99%